Value of WTO Trade Agreements in a New Keynesian Model - Ganelli, Giovanni (IMF Working Papers; Working Paper ;, 2015)
We revisit the question of the quantitative benefits of WTO trade agreements in a setup that is non-standard from the traditional trade policy point of view. We show that in a New Keynesian model, unilateral trade liberalization reduces welfare due to terms-of-trade deterioration, creating an incentive for a trade agreement. For realistic parameter values, the value of an agreement, which cuts tariffs by one percentage point, is 0.5% to 2% of consumption, much larger than in trade models. The intuition for this result hinges on some New Keynesian features of our framework, such as imperfect competition and endogenous labor supply.